The Analysis of Property Loans Development in Indonesia - Anisa Nurpita; Rina Oktavia (Universitas Ahmad Dahlan, 2021)
The property sector in Indonesia has an essential role in driving the national economy. The bank lending development to the property sector in April 2019 did not show significant growth and stagnant. This study analyzes the growth trend of property loans in Indonesia and estimates the factors that affect the number of housing loans (KPR) and apartment ownership loans (KPA) in Indonesia. The data used in this study are secondary data and time series. The analytical tools used in this research are trend and regression. The results showed that from 2020 to 2025, the property loan growth in Indonesia will still be sluggish. The condition is identified by construction loan which is expected to grow even though the increase is not too significant, real estate loan is still fluctuating, this is because in 2019 there was a decline in real estate loan growth of almost 50 percent from the previous year, and KPA and KPR are estimated to decline even though in nominal terms the number of KPR and KPA increases. The population number variable has a positive and significant effect on the number of KPR and KPA in Indonesia. The more the population, the more the number of KPR and KPA will increase. Meanwhile, the variables of economic growth and inflation in this study did not significantly affect the number of KPR and KPA.